Varredura molecular de polimorfismos associados à resistência aos benzimidazóis em Ascaris lumbricoides - Celi da Silva Medeiros (2018)
Ascaris lumbricoides is a parasite of great medical importance and has a wide geographical distribution, being found in almost every country in the world. Ascaridosis is one of the parasitic diseases that is among the most common and neglected infections worldwide, affecting poorer and disadvantaged communities. In 2001, the World Health Assembly, World Health Organization's principal decision-making body, adopted a resolution WHA54.19, which encourages endemic countries to develop effective policies to combat parasitic diseases. Periodic treatment of people living in endemic areas, mainly children, with the mass administration of anti-helminthic drugs (MDA) was instituted. The treatment significantly reduced the prevalence of moderate and high intensity infections in children. However, MDA can select subpopulations with genetic ability to survive treatment. Mutations in codons 167, 198 and 200 of the β-tubulin isotype 1 gene are associated with resistance to benzimidazoles in some nematodes of veterinary importance. Polymorphisms associated with resistance have already been described for the species Ascaris lumbricoides, Trichuris trichiura and hookworms. However, these studies are rare, and polymorphism in the β-tubulin gene of these parasites has never been performed in Brazil. Thus, this project carried out a search for polymorphisms in the β-tubulin isotype 1 gene of Ascaris lumbricoides in human stool samples from patients from six Brazilian states (Bahia, Ceará, Maranhão, Minas Gerais, Piauí and Tocantins). Nested-PCR reactions were performed on 864 samples from individual eggs obtained from 62 patients. From the nested-PCR products, 601 PCR-RFLP reactions were performed for each codon, 167 and 198. Some samples presented a suggestive profile of mutations for the two codons and were submitted to DNA sequencing. Fifty-two samples were sequenced and it was found that no SNP was detected for codons 167 and 198 in the Ascaris lumbricoides samples analyzed for the six Brazilian states. These results are in line with data recently published in a study in Rwanda, which also found no mutation in the analyzed samples and that came from patients who failed albendazole treatment. The results of this work together with data from the literature reinforce the need for further studies on the subject of anthelmintic resistance to soil transmitted parasites and the search for elucidation of the relationships between the low efficacy of benzimidazoles for the treatment of some nematodes and the possible involved causes, molecular or metabolic.